„Robin Hood” Government: Some Sociological Considerations - Sabin Drăgulin (Sfera Politicii, 2011)
After two decades after the collapse of the communist state, the „social state” enjoys great popularity in our country. This article aims to present some general undesirable consequences of redistributive social policy, less evident in the current public and political debate, which seems dominated by the idea that (increasing) redistribution of revenues is always desirable.